Questions and answers for electricians examinations - Anderson, Edwin P.; Palmquist, Roland E. (Indianapolis, Indiana: Theodore Audel & Co., 1969)
This book is offered as a guide for anyone preparing for the various electricians' license examinations- apprentice, journeyman, or master. Numerous examples in the form of questions and answers are presented throughout this book, thereby enabling the license applicant to gain a complete knowledge of the types of questions asked in an electricians' examination.
1945, 1952, 1958, 1961, and 1965 editions published under title: Audels questions and answers for electricians examinations.
Includes index.
ne 3/05/2018
Arch
Keywords: Electrical Engineering